Neurological Outcome at 30 Months of Age after Mild Hypothermia via Selective Head Cooling in Term Neonates with Perinatal Asphyxia Using Low-Cost CoolCap: A Single-Center Randomized Control Pilot Trial in India - Das, Suman; Sarkar, Nirmalya; Bhattacharya, Mala; Basu, Suprit; Sanyal, Debashish; Chatterjee, Anish; Aich, Bholanath; Chatterjee, Kaushani (Journal of Pediatric Neurology, 2017)
The objective of this study was to determine the effectiveness and safety of mild systemic hypothermia by selective head cooling in hospital born neonates with hypoxic-ischemic encephalopathy using low-cost CoolCap. The primary outcome was to determine whether selective head cooling reduces neonatal mortality and neurodevelopmental delay (NDD) at > 30 months of age. The secondary outcome was to determine the serious adverse effects during selective head cooling such as thrombocytopenia requiring platelets transfusion, renal and hepatic dysfunction, bradycardia, hypoglycemia, and dyselectrolytemia (hyperkalemia, hyponatremia, and hypocalcemia). This is a single-center randomized control trial. The risk ratios, risk differences, and numbers needed to treat plus 95% confidence interval (CI) were measured. This study was done at the tertiary care perinatal center. Inborn neonates with ≥ 37 completed weeks of gestation with indicators of perinatal asphyxia and moderate to severe clinical encephalopathy were randomly allocated to hypothermia (n = 30) or standard care (n = 30) groups. The neonates were subjected to mild systemic hypothermia via selective head cooling using ice caps, the target rectal temperature being 34 to 35°C for 72 hours. Therapeutic hypothermia reduced the risk of death and NDD at ≥ 30 months of age: 6 of 30 infants (20%) in the hypothermia group and 18 of 30 infants (60%) in the control group died or had a NDD at ≥ 30 months (risk ratio: 0.33 [95% CI: 0.15–0.72]; p = 0 0.0015). The mortality rate decreased, and the survival rate free of any sensorineural disability increased. The benefits were statistically significant in moderately asphyxiated infants. Adverse effects of hypothermia were minimal. Selective head cooling with mild systemic hypothermia in term asphyxiated neonates is safe and inexpensive in low-resource setting. Hypothermia showed statistically significant reduction in mortality and NDD at ≥ 30 months of age when commenced within 6 hours of birth and was not associated with serious adverse effects. The Institutional Clinical Trial Registry number is CNMC/ETHI/317/P.
Keywords: perinatal asphyxia; ice cap; selective head cooling; neurodevelopmental delay; Developmental Assessment Scale for Indian Infants